If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 58 = 5m + 52 Reorder the terms: 58 = 52 + 5m Solving 58 = 52 + 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. 58 + -5m = 52 + 5m + -5m Combine like terms: 5m + -5m = 0 58 + -5m = 52 + 0 58 + -5m = 52 Add '-58' to each side of the equation. 58 + -58 + -5m = 52 + -58 Combine like terms: 58 + -58 = 0 0 + -5m = 52 + -58 -5m = 52 + -58 Combine like terms: 52 + -58 = -6 -5m = -6 Divide each side by '-5'. m = 1.2 Simplifying m = 1.2
| 14z-2/7=5/7 | | (7x+5)+(9x+2)=81 | | 2x+(-2x+1)=1 | | 6m+54=4m | | -87=-5x-3x+9 | | 16+18=4x-6 | | x^2=16/0.49 | | 8m+60=20m | | 2/5a-42 | | 32r+4s=36r | | S+15=8 | | -2x-3+-3x=17 | | 20.8+2z=24 | | 7t=80+91 | | 17/12m=1/2m-11/4 | | 6x-4(4+2x)=-10(3x+10) | | -2x^2-4x+24=0 | | Y=45x+145 | | 2+11b= | | 10-2x=25 | | y=3y+8 | | 8-7x+2x=38 | | 50+3(x+6)=4x-5 | | 10-11(4+n)=8(7-7n) | | 4x-2x+6xy+21x+(-9)-9= | | 2x^2+9x-396=0 | | 1/2x-8=-5 | | -6(x+9)-9x=-3(x+2) | | 9x+9=5x+6 | | 3(6x+4)=6(-2x+5x+4) | | 6x+40-10x=100 | | (8a-5+1)=8-2(a-3) |